High thermoelectric performance in (Bi0.25Sb0.75)2Te3 due to band convergence and improved by carrier concentration control. Issue 8 (October 2017) - Kim, Hyun-Sik; Heinz, Nicholas A.; Gibbs, Zachary M.; Tang, Yinglu; Kang, Stephen D.; Snyder, G. Jeffrey
Abstract : Bi2 Te3 has been recognized as an important cooling material for thermoelectric applications. Yet its thermoelectric performance could still be improved. Here we propose a band engineering strategy by optimizing the converging valence bands of Bi2 Te3 and Sb2 Te3 in the (Bi1− x Sb x )2 Te3 system when x  = 0.75. Band convergence successfully explains the sharp increase in density-of-states effective mass yet relatively constant mobility and optical band gap measurement. This band convergence picture guides the carrier concentration tuning for optimum thermoelectric performance. To synthesize homogeneous textured and optimally doped (Bi0.25 Sb0.75 )2 Te3, excess Te was chosen as the dopant. Uniform control of the optimized thermoelectric composition was achieved by zone-melting which utilizes separate solidus and liquidus compositions to obtain zT  = 1.05 (at 300 K) without nanostructuring.